Studies on Ulva fasciata and Chaetomorpha antennina from Tenneti Park, Visakhapatnam Coastal Area, India - Prasanthi , Ch.; Kumari , Sr. Prema; Jahnavi , K.; Swapna , D.; Omkari , D.; Rupa , D.; Mounika , K.; Jayasri , D.; Shanmuki , K.; Madhushalini, G.; Vasavi, B.; Yamini , P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Seaweed is considered as herbal medicine and food source utilized by the coastal community. Seaweed is commonly consumed because it is an important source of iodine. Ulva fasciata and Chaetomorpha antennina are green seaweed wildly grow in marine environment. Green algae are involved in photosynthetic reaction. These are observed worldwide. These algal blooms are a consequence of human activities. Phytochemical compounds are secondary metabolite groups in living organisms that have a certain function for humans. Algae are known to contain a huge variety of bioactive compounds having high potentiality towards medical field. They are seen mainly in shallow waters with high degree of salinity. Now-a-days they have commercially important with their valuable components in the form of as bioactive compounds. The objective of this study was to analyse the potential anti-bacterial activity and antifungal activity, the presence of phytochemical and biomolecules in U. fasciata and C. antennina. The samples of U. fasciata and C. antennina was collected aseptically from Tenneti park, Visakhapatnam coastal zone. The research phase includes solvent extraction, phytochemical screening, and antibacterial activity. The zone of inhibition ranges from 0.5nm to 0.7nm by the U. fasciata extracts whereas the extracts from C. antennina ranges from 0.2nm to 0.3 nm. The presence of phytochemicals was observed in both the green seaweeds. The present study is biofuel extraction from the 2 seaweed extracts. The findings gave a result that C. antennina have high potentiality of biofuel production.